PKG1α Cysteine-42 Redox State Controls mTORC1 Activation in Pathological Cardiac Hypertrophy. Issue 4 (31st July 2020) - Oeing, Christian U.; Nakamura, Taishi; Pan, Shi; Mishra, Sumita; Dunkerly-Eyring, Brittany L.; Kokkonen-Simon, Kristen M.; Lin, Brian L.; Chen, Anna; Zhu, Guangshuo; Bedja, Djahida; Lee, Dong Ik.; Kass, David A.; et al.
Abstract : Rationale: Stimulated PKG1α (protein kinase G-1α) phosphorylates TSC2 (tuberous sclerosis complex 2) at serine 1365, potently suppressing mTORC1 (mechanistic [mammalian] target of rapamycin complex 1) activation by neurohormonal and hemodynamic stress. This reduces pathological hypertrophy and dysfunction and increases autophagy. PKG1α oxidation at cysteine-42 is also induced by these stressors, which blunts its cardioprotective effects. Objective: We tested the dependence of mTORC1 activation on PKG1α C42 oxidation and its capacity to suppress such activation by soluble GC-1 (guanylyl cyclase 1) activation. Methods and Results: Cardiomyocytes expressing wild-type (WT) PKG1α (PKG1α WT ) or cysteine-42 to serine mutation redox-dead (PKG1α CS/CS ) were exposed to ET-1 (endothelin 1). Cells expressing PKG1α WT exhibited substantial mTORC1 activation (p70 S6K [p70 S6 kinase], 4EBP1 [elF4E binding protein-1], and Ulk1 [Unc-51-like kinase 1] phosphorylation), reduced autophagy/autophagic flux, and abnormal protein aggregation; all were markedly reversed by PKG1α CS/CS expression. Mice with global knock-in of PKG1α CS/CS subjected to pressure overload (PO) also displayed markedly reduced mTORC1 activation, protein aggregation, hypertrophy, and ventricular dysfunction versus PO in PKG1α WT mice. Cardioprotection against PO was equalized between groups by co-treatment with the mTORC1 inhibitor everolimus. TSC2-S1365 phosphorylation increased in PKG1α CS/CS more than PKG1α WT myocardium following PO. TSC2 S1365A/S1365A (TSC2 S1365 phospho-null, created by a serine to alanine mutation) knock-in mice lack TSC2 phosphorylation by PKG1α, and when genetically crossed with PKG1α CS/CS mice, protection against PO-induced mTORC1 activation, cardiodepression, and mortality in PKG1α CS/CS mice was lost. Direct stimulation of GC-1 (BAY-602770) offset disparate mTORC1 activation between PKG1α WT and PKG1α CS/CS after PO and blocked ET-1 stimulated mTORC1 in TSC2 S1365A -expressing myocytes. Conclusions: Oxidation of PKG1α at C42 reduces its phosphorylation of TSC2, resulting in amplified PO-stimulated mTORC1 activity and associated hypertrophy, dysfunction, and depressed autophagy. This is ameliorated by direct GC-1 stimulation. Abstract : Supplemental Digital Content is available in the text.